Penggunaan Larutan Bio CAS untuk Meningkatkan Kandungan Protein dan Menurunkan Kandungan Serat Kasar Jerami Padi melalui proses fermentasi: The Use of Bio CAS Solvent to Increase The Protein Content and Decrease The Crude Fiber Content of Rice Straw through Fermentation Process (Emasains : Jurnal Edukasi Matematika dan Sains, 2019)
This research aims to find out the effects of using Bio CAS solvent on the protein content and the reduction of crude fiber content through fermentation process. The collected data were the protein content and the crude fiber, also physical observation of the rice straw assessed by 20 respondents on the colors, textures and smell. The data were treated using the analysis of variance (ANAVA) by performing the F test at the significance level of 5% and 1%. The Duncant test would be performed if there happen to be any significant differences between the treatments. The most optimal result of the fermented protein content was in P3 treatment at the concentration of 2% with the value of 6,0571%. The lowest crude fiber content occured in the treatment with a concentration of 2% (P3) with a value of 24,2873% and the P3 treatment also had a weak texture, the color of the rice straw was brownish yellow and smelled of acid like the smell of tape.